2015
DOI: 10.1016/j.jneuroim.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

IgG1 deficiency exacerbates experimental autoimmune myasthenia gravis in BALB/c mice

Abstract: Myasthenia gravis is an autoimmune disease characterized by muscle weakness due to neuromuscular junction (NMJ) damage by anti-acetylcholine receptor (AChR) auto-antibodies and complement. In experimental autoimmune myasthenia gravis (EAMG), which is induced by immunization with Torpedo AChR in CFA, anti-AChR IgG2b and IgG1 are the predominant isotypes in the circulation. Complement activation by isotypes such as IgG2b plays a crucial role in EAMG pathogenesis; this suggested the possibility that IgG1, which d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In line with the above mentioned findings, it has recently been demonstrated that IgG1-deficient mice develop severe autoimmune conditions in different inflammatory autoimmune disease models ( 63 , 64 ) as well as enhanced antigen-dependent IgG3 IC depositions in the kidneys ( 37 ). The autoimmune models used in these studies ( 63 , 64 ), similar to other inflammatory autoimmune models, are apparently dependent on C1q and the complement activation as well as on classical FcγR-mediated immune cell activation ( 21 , 61 , 63 69 ). In future studies, it would be important to explore the inhibitory potential of murine IgG1 and its Fc glycosylation status in terms of the complement activation and FcγR-mediated regulation of effector cells using various models of autoimmunity and inflammation.…”
Section: Discussionsupporting
confidence: 71%
“…In line with the above mentioned findings, it has recently been demonstrated that IgG1-deficient mice develop severe autoimmune conditions in different inflammatory autoimmune disease models ( 63 , 64 ) as well as enhanced antigen-dependent IgG3 IC depositions in the kidneys ( 37 ). The autoimmune models used in these studies ( 63 , 64 ), similar to other inflammatory autoimmune models, are apparently dependent on C1q and the complement activation as well as on classical FcγR-mediated immune cell activation ( 21 , 61 , 63 69 ). In future studies, it would be important to explore the inhibitory potential of murine IgG1 and its Fc glycosylation status in terms of the complement activation and FcγR-mediated regulation of effector cells using various models of autoimmunity and inflammation.…”
Section: Discussionsupporting
confidence: 71%
“…Serum levels of anti-AChR IgG2b (predominant and pathogenic isotype) in EAMG mice were measured using ELISA 72 h post 3rd treatment using our affinity-purified mouse muscle AChR (coating antigen), rat antimouse IgG2b-HRP (secondary Ab; BD Bioscience, CA), and ABTS (2'azino-bis 3-ethylbenzthiazoline-6-sulfonic acid) (Invitrogen, MA) as substrate ( 33 ). To check if HDAC inhibition - mediated Ab reduction had a time-dependent reversal, EAMG mice were bled at 4 weeks post 3rd (last) treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Functional muscle-AChR content reliably represents the treatment effect on muscle strength of EAMG mice ( 33 ). We standardized a new ELISA method alternative to radioimmunoassay for quantitating the relative abundance of functional AChR in the proximal forelimb muscles that are affected most in EAMG.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicated that IgG4 might be involved in the pathogenesis of IgAN. The IgG1 of mice, which cannot activate complement, is similar to human IgG4 in function and Th2-dependency (4,23). Mice deficient in IgG1 were reported as more vulnerable to MG, arthritis, and lethal renal disease under corresponding stimulations, the other IgG isotypes which can activate complement were frequently elevated in these disorders.…”
Section: Decreased Igg4 + B and Th2 Cells In Iganmentioning
confidence: 98%
“…Mice deficient in IgG1 were reported as more vulnerable to MG, arthritis, and lethal renal disease under corresponding stimulations, the other IgG isotypes which can activate complement were frequently elevated in these disorders. Simultaneously, the additional injection of antigen-specific IgG1 was shown to protect mice from diseases through the inhibition of IC formation (23)(24)(25). The effect of mouse IgG1 presumably applies to human IgG4.…”
Section: Decreased Igg4 + B and Th2 Cells In Iganmentioning
confidence: 99%